Analysis and characterization of extra virgin olive oils - Checchetti, Andrea; Martano, Donato; Veltri, Rosagnela (Open Schools Journal for Open Science, 2018)
Samples of extra virgin olive oils obtained from the olive trees of the territory of San Giovanni in Fiore (CS), Italy, and samples common brands of extra virgin olive oils sold on the national territory, have been analysed according to EU regulation n. 61/2011 of the Commission of 24 January 2011. The extra virgin oils examined were characterized by investigating their acidity, the number of peroxides, the rancidity, and the spectrophotometric parameters that provide useful elements for assessing the composition and the quality. Furthermore, the infrared analysis provides useful data that help carry out quality control.